STAGES AND EXERCISES FOR DEVELOPMENT OF READING SKILLS - Boxodirova Komilaxon Xamidjon qizi; Qo’chqorova Zulfizar Abduhamidovna (Лучшие интеллектуальные исследования, 2023)
Abstract: Reading is a fundamental skill that plays a crucial role in our lives. It is not only the ability to decode and comprehend written text but also an essential element of education, information, and communication. Developing reading skills begins at an early age and continues throughout our lives. In this article, we will explore the key stages of reading development and suggest exercises for each stage.